Language and Thought in the Era of Artificial Intelligence: A Philosophy of Science Inquiry into the New Linguistic Paradigm in Arabic Language Education - Imtiyaz, Indy; Bakar, M. Yunus Abu; Fathoni (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
The development of Artificial Intelligence (AI) has introduced fundamental changes in the relationship between language and thought, generating significant epistemological implications for Arabic language education. This article aims to analyze the relationship between language and thought from a philosophy of science perspective in the AI era, identify conceptual gaps in technology-based learning practices, and formulate a more reflective and integrative linguistic paradigm. The study employs a qualitative approach through library research, utilizing content analysis of sources in philosophy of language, educational technology, and Arabic pedagogy. The findings indicate that AI encourages a shift from a transmissional toward a constructive-dialogical epistemology, in which knowledge is produced through interactions between humans and technology. Although AI enhances learning effectiveness and personalization, the interpretation of language still requires human reflective consciousness. Therefore, Arabic language education should develop a humanistic-digital approach that positions technology as an epistemic partner without displacing the role of language as a medium for constructing meaning, awareness, and values.